Disability inclusive elections in Africa: a systematic review of published and unpublished literature. Issue 4 (21st April 2018) - Virendrakumar, Bhavisha; Jolley, Emma; Badu, Eric; Schmidt, Elena
Abstract: The United Nations Convention on the Rights of Persons with Disabilities underscores the equal right of persons with disabilities to participate in political life. However, in Africa they are often unable to exercise their right to vote. This study sought to systematically review available evidence on inclusive elections in Africa. Findings showed that although most African countries ratified disability-focused legislation and proclaimed equal opportunities, the implementation of the legislation varies across the continent. Barriers to political participation can occur at any electoral stage and can be broadly categorised into three groups: lack of education and financial resources; stigma and negative social attitudes; and inaccessible physical infrastructure.